Context-Aware Markov Sensors and Finite Mixture Models for Adaptive Stochastic Dynamics Analysis of Tourist Behavior - Xiaolong Chen; Hongfeng Zhang; Cora Un In Wong; Zhengchun Song (Mathematics, 2025)
We propose a novel framework for adaptive stochastic dynamics analysis of tourist behavior by integrating context-aware Markov models with finite mixture models (FMMs). Conventional Markov models often fail to capture abrupt changes induced by external shocks, such as event announcements or weather disruptions, leading to inaccurate predictions. The proposed method addresses this limitation by introducing virtual sensors that dynamically detect contextual anomalies and trigger regime switches in real-time. These sensors process streaming data to identify shocks, which are then used to reweight the probabilities of pre-learned behavioral regimes represented by FMMs. The system employs expectation maximization to train distinct Markov sub-models for each regime, enabling seamless transitions between them when contextual thresholds are exceeded. Furthermore, the framework leverages edge computing and probabilistic programming for efficient, low-latency implementation. The key contribution lies in the explicit modeling of contextual shocks and the dynamic adaptation of stochastic processes, which significantly improves robustness in volatile tourism scenarios. Experimental results demonstrate that the proposed approach outperforms traditional Markov models in accuracy and adaptability, particularly under rapidly changing conditions. Quantitative results show a 13.6% improvement in transition accuracy (0.742 vs. 0.653) compared to conventional context-aware Markov models, with an 89.2% true positive rate in shock detection and a median response latency of 47 min for regime switching. This work advances the state-of-the-art in tourist behavior analysis by providing a scalable, real-time solution for capturing complex, context-dependent dynamics. The integration of virtual sensors and FMMs offers a generalizable paradigm for stochastic modeling in other domains where external shocks play a critical role.